Representasi Altruisme Wartawan Perang dalam Film “Civil War” (Analisis Semiotika Roland Barthes) - Salim, Alfiansyah (Jurnal Spektrum Komunikasi, 2024)
Civil War is a dystopian genre film produced by A24, which explores the theme of the American Civil War from the perspective of a war correspondent. The film showcases the dedication of war journalists in reporting events at the front lines as a form of altruistic value. This study aims to examine and elaborate on the representation of the altruistic values of war correspondents depicted in Civil War. The research will employ a constructivist paradigm, a qualitative approach, Roland Barthes' semiotic analysis method, and will be descriptive in nature. The study focuses on scenes that portray attitudes representing the altruism of war correspondents. The findings reveal four attitudes representing the altruistic values of war correspondents in Civil War: helping colleagues, high dedication, disregarding personal risk, and concern for mental health.